1997
DOI: 10.1016/s0031-9384(97)00011-5
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Behaviour and Testosterone Concentration in Immunodepressed Male Laboratory Mice (Mus musculus)

Abstract: . Modulation of behaviour and testosterone concentration in immunodepressed male laboratory mice (Mus musculus). PHYSIOL BEHAV 61(6) 907-917, 1997.-Recent ideas suggest that current immunocompetence may act as a constraint on behavioural and physiological decisions, where these risk imposing an additional burden on immune function. We tested this in the context of time budgeting and the secretion of the potentially immunodepressive hormones testosterone and corticosterone, by treating adult male CFLP laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 31 publications
(57 reference statements)
1
19
0
Order By: Relevance
“…Like other studies (Macrides et al 1975;Bronson 1979;Barnard et al 1997;Moshkin et al 2001Moshkin et al , 2004Amstislavskaya & Popova 2004;Nyby 2008), we observed several behavioral effects of female odor: male mice from the scent-treated group had a clear sniffing response to the bedding from female cages, and they concentrated their marking activity near female scent stimuli; and scenttreated male mice had more wounds as an indicator of higher inter-male aggression in comparison with male mice isolated from female odor. In addition, our results demonstrated that exposure to female olfactory signals results in increasing masses of preputial glands and seminal vesicles and a declining thymus mass.…”
Section: Disscussionsupporting
confidence: 84%
“…Like other studies (Macrides et al 1975;Bronson 1979;Barnard et al 1997;Moshkin et al 2001Moshkin et al , 2004Amstislavskaya & Popova 2004;Nyby 2008), we observed several behavioral effects of female odor: male mice from the scent-treated group had a clear sniffing response to the bedding from female cages, and they concentrated their marking activity near female scent stimuli; and scenttreated male mice had more wounds as an indicator of higher inter-male aggression in comparison with male mice isolated from female odor. In addition, our results demonstrated that exposure to female olfactory signals results in increasing masses of preputial glands and seminal vesicles and a declining thymus mass.…”
Section: Disscussionsupporting
confidence: 84%
“…At the end of the period of pre-weaning observation, pups were separated from their mothers (weaning) and each mother and pup were weighed for the second time. At this point the ¢rst 88-ml blood sample (sample 1) was taken retro-orbitally from each pup following the procedure of Barnard et al (1997a). Pups were then maintained in their natal litters for a further 50 days and behaviours recorded as during the pre-weaning phase (but minus interactions with the dam and suckling behaviour) on 19 d spread through the post-weaning period.…”
Section: (B) Post-weaning Procedures (Phase 2 )mentioning
confidence: 99%
“…As in our previous work (e.g. Barnard et al 1997aBarnard et al ,b, 1998, high-and low-rank categories within random groups were de¢ned on the basis of the ratio of attacks (Bite, Chase, O¡ensive upright, O¡ensive sideways and/ or Circling in table 1 of Barnard et al (1997a,b)) initiated and received by each male during the period of grouping. As before, high-ranking males were identi¢able as having high initiation-to-receipt ratios and initiating signi¢cantly and disproportionately more attacks (F 1,60 31.35, p50.0001).…”
Section: (A) Rank Categoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, as discussed by Bohus and Koolhaas (1991), exposure to environmental and social stressors can lead to immunosuppression and therefore increased susceptibility to infection. In captivity, aggression in male rodents can be triggered by female scent alone (Barnard et al 1997). Therefore, it is possible that even though the male mice in this study were not housed in cages with females, the scent of the females in close proximity may have increased aggression and investment in courtship behaviours among the male mice.…”
Section: Discussionmentioning
confidence: 99%